Clinicopathological features of primary fallopian tube carcinoma: A single institution experience - Papadimitriou, C.A.; Markaki, S.; Lianos, E.; Peitsidis, P.; Vourli, G.; Nikitas, N.; Vlachos, G.; Rodolakis, A.; Antsaklis, A.; Dimopoulos, M.A. (European Journal of Gynaecological Oncology, 2009)
Purpose of investigation: Primary fallopian tube carcinoma (PFTC) is a rare malignancy with only few data existing on the impact of prognostic factors. Methods: We retrospectively analyzed 26 patients. Tissue blocks were reviewed and sections were stained for vascular endothelial growth factor (VEGF), matrix metalloproteinases 2 and 9 (MMP-2, MMP-9), tissue inhibitors of metalloproteinases 1 and 2 (TIMP-1, TIMP-2), c-erbB-2, estrogen (ER), and progesterone receptors (PgR). Results: Reactivity for VEGF, ER, PgR, MMP-2, MMP-9, TIMP-1, TIMP-2 and c-erbB-2 was observed in 85%, 46%, 27%, 11.5%, 58%, 0%, 23% and 8% of specimens, respectively. None of the markers studied displayed prognostic significance. Regarding clinical prognostic factors, the hazard ratio (HR) for progression and death for patients with tumor residuum > 2 cm was 5.24 (p < 0.01) and 11.19 (p < 0.005), respectively. Patients with advanced stage disease had a HR of 12.55 (p < 0.05) for progression, while the HR for death was not found to be statistically significant. Conclusion: None of the biomarkers studied seems to influence survival. Early-stage disease and optimal debulking are associated with improved outcome.
Keywords: First-line chemotherapy; Immunohistochemistry; Primary fallopian tube cancer; Prognostic factors